THE ECONOMIC CONTENT AND SIGNIFICANCE OF THE EFFICIENCY OF USING INNOVATIVE TECHNOLOGIES IN THE DIGITAL TRANSFORMATION OF AGRICULTURE (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes the economic content and significance of the efficiency of using innovative technologies in the context of agricultural digital transformation. The study explores opportunities for increasing productivity, improving resource utilization, and reducing production costs by integrating digital technologies into agricultural production processes.